Dampak Makro Ekonomi Dan Financial Performance Terhadap Market Share Perbankan Syari'ah Di Indonesia - Muh. Khairul Fatihin; Eko Siswahto; Sulistya Rusgianto; Nizar Hosfaikoni Hadi (Jurnal Ekonomi, 2020)
Islamic banking market share is the biggest contributor to the development of the Islamic financial market share. This study aims to comprehensively examine the sharia banking market share growth in short-term and long-term dynamic interactions. The independent variables used in this study are inflation, industrial production index (IPI), interest rate, Return of Assets (ROA) and financing to Deposit Ratio (FDR). The method used is the Autoregressive Distributed Lag Model (ARDL) with monthly data from 2011-2018. The results of this study indicate that interest rates have a significant negative effect on Islamic banking market share in the short and long term. Meanwhile, inflation, ROA, FDR have a positive effect on the sharia banking market share in the short term. IPI's industrial production index as a proxy for the domestic product (gross domestic product) has no short-term and long-term impact. The results of this study have important implications for the central bank and the banking sector.